1998
DOI: 10.1007/s002530051285
|View full text |Cite
|
Sign up to set email alerts
|

Antimould activity of sourdough lactic acid bacteria: identification of a mixture of organic acids produced by Lactobacillus sanfrancisco CB1

Abstract: Sourdough lactic acid bacteria, cultivated in wheat flour hydrolysate, produced antimould compounds. The antimould activity varied greatly among the strains and was mainly detected within obligately heterofermentative Lactobacillus spp. Among these, Lb. sanfrancisco CB1 had the largest spectrum. It inhibited moulds related to bread spoilage such as Fusarium, Penicillium, Aspergillus and Monilia. A mixture of acetic, caproic, formic, propionic, butyric and n-valeric acids, acting in a synergistic way, was respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
162
0
9

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(190 citation statements)
references
References 10 publications
13
162
0
9
Order By: Relevance
“…The increasing knowledge of sourdough ecology is leading to the improvement of the quality of the end product through the use of starter cultures with enhanced technological capabilities, such as exopolysaccharide production (Korakli et al, 2003;Lacaze et al, 2007), antifungal activity (Corsetti et al, 1998b;Schnürer & Magnusson, 2005), antistaling properties (Corsetti et al, 2000;Moore et al, 2007) and decreased gluten intolerance (Di Cagno et al, 2005;Gobbetti et al, 2007). The identification of L. sanfranciscensis at strain level proves to be crucial as a consequence of the rising interest in the above-mentioned strain-related functional traits and for monitoring patented technologies in sourdough production.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing knowledge of sourdough ecology is leading to the improvement of the quality of the end product through the use of starter cultures with enhanced technological capabilities, such as exopolysaccharide production (Korakli et al, 2003;Lacaze et al, 2007), antifungal activity (Corsetti et al, 1998b;Schnürer & Magnusson, 2005), antistaling properties (Corsetti et al, 2000;Moore et al, 2007) and decreased gluten intolerance (Di Cagno et al, 2005;Gobbetti et al, 2007). The identification of L. sanfranciscensis at strain level proves to be crucial as a consequence of the rising interest in the above-mentioned strain-related functional traits and for monitoring patented technologies in sourdough production.…”
Section: Introductionmentioning
confidence: 99%
“…Magnusson and Schnürer (12) described production of a proteinaceous antifungal compound by a Lactobacillus coryniformis strain, while Lavermicocca et al (10) reported isolation of the antifungal compounds phenyllactic acid and 4-hydroxyphenyllactic acid from Lactobacillus plantarum. Short-chain fatty acids, in particular caproic acid, produced by the sourdough bacterium Lactobacillus sanfrancisco also exhibit anti-mold activities (1). L. plantarum can produce fungus-inhibitory low-molecular-weight substances, such as benzoic acid, methylhydantoin, mevalonolactone, and cyclo-(Gly-L-Leu) (14), while a fungistatic bacteriocin-like substance, pentocin TV35b, was isolated from a Lactobacillus pentosus strain (15).…”
mentioning
confidence: 99%
“…sanfrancisco CB1. The acids include acetic, caproic, formic, propionic, butyric and n--valeric acids, that acted synergistically in inhibiting mold growth (Corsetti et al, 1998). Similar results were also found by Magnusson and Schnurer (2001).…”
Section: Anti--mold Activity Of Supernatant and The Physicochemical Csupporting
confidence: 76%
“…Corsetti et al (1998) studied the mixture of organic acids produced by Lactobacillus sanfrancisco CB1, and found that the organic acids act in a synergistic way and that caproic acid played a key role in increasing the antifungal activity of the mixture.…”
Section: Organic Acidsmentioning
confidence: 99%